Fermentative Characteristics and Metabolic Profiles of Japanese Apricot Juice Fermented with Lactobacillus acidophilus and Torulaspora delbrueckii - Benjawan Papun; Pairote Wongputtisin; Apinun Kanpiengjai; Tippapha Pisithkul; Phayungsak Manochai; Kamonwan Manowan; Anong Atsaneechantra; Ni-orn Chomsri (Foods)
Functional fermented fruit juices produced using a combination of non-Saccharomyces yeast and lactic acid bacteria (LAB) are relatively unexplored. The effects of three inoculation protocols, single inoculation with Lactobacillus acidophilus (La), single inoculation with Torulaspora delbrueckii (Td), and co-culture of both La + Td, on the physicochemical, microbiological, sensory properties, and metabolic profile of fermented JA juices after 24 h at 30 °C were investigated. Uninoculated (UI) Japanese apricot (JA) juice was used as a control. The results show significant increases in the color intensity of the fermented-JA juices, whereas an enhancement of total phenolic contents is observed in the fermented JA-juices acquired through the use of La for both single and co-culture inoculations. The colony counts of LAB and yeast in the inoculated JA juices increased by approximately 2.0 and 1.7 log CFU/mL at 24 h, respectively. The antibacterial activity of JA juices against four pathogenic bacteria was detected. All JA juices exhibited antimicrobial activity against the tested pathogenic strains, with strong antibacterial properties of La-fermented juice being recorded against Bacillus cereus at the lowest MIC of 124 µL/mL. Additionally, La + Td-fermented and UI-JA juices demonstrated comparable anticancer activity against HT-29 cells with IC50 values of 823.37 and 754.87 µg/mL, respectively. Furthermore, a total of 995 compounds was identified as differential fermentation metabolites through non-targeted metabolome analysis across different fermentation groups. These findings illustrate the significant potential of using JA juice for La and Td fermentation to develop functional juices.